2022
DOI: 10.1111/jam.15443
|View full text |Cite
|
Sign up to set email alerts
|

Structure and functional capacity of a benzene-mineralizing, nitrate-reducing microbial community

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Pseudomonadaceae (0 -21%)), and unknown Rhizobiaceae (0 -0.2%), Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium (0 -0.2%) (Family: Rhizobiaceae (< 1%)) were detectable at the indicated range of relative abundances throughout the time-course of the previous study done with the original inoculum (Eziuzor et al, 2022). Thus, the corresponding phylotypes identified in acetate-grown consortia showed a snapshot of possible isolates under the classical isolation procedure employed here.…”
Section: : Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Pseudomonadaceae (0 -21%)), and unknown Rhizobiaceae (0 -0.2%), Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium (0 -0.2%) (Family: Rhizobiaceae (< 1%)) were detectable at the indicated range of relative abundances throughout the time-course of the previous study done with the original inoculum (Eziuzor et al, 2022). Thus, the corresponding phylotypes identified in acetate-grown consortia showed a snapshot of possible isolates under the classical isolation procedure employed here.…”
Section: : Discussionmentioning
confidence: 91%
“…The copyright holder for this preprint this version posted January 7, 2023. ; https://doi.org/10.1101/2023.01.07.522375 doi: bioRxiv preprint fixing symbionts mostly found naturally in legumes (Mousavi et al, 2014) and have been identified in anaerobic microbial communities degrading acetate under sulfate-reducing conditions (Bin Hudari et al, 2020), and benzene under nitrate-reducing conditions (Eziuzor et al, 2022), which is the original inoculum for the isolation attempt. ANPR was also found to be the dominant phenanthrene degrader aerobically in gradient anthropized soils (Lemmel et al, 2019).…”
Section: : Discussionmentioning
confidence: 99%
See 3 more Smart Citations